Design and implementation of DC linear actuator and stepper motor for remote control of the driverless tractor robot - Viroch Sukontanakarn; Tanawat Chalardsakul; Banjerd Saengchandr (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
This research was to propose the DC linear actuators and a stepper motor as mechanical drive systems such as brake pedal, clutch pedal, forward-reverse gearshift, gear position selection, tail-lifting system to lift the chemical tank, and the speed selection system of power take-off (PTO). The DC linear actuators were used instead of the muscles, arms, and legs of the human being. The stepper motor was used to control the steering direction of a driverless tractor robot. The control was based on the programmable logic controller and radio remote control for the driverless tractor robots. Both MATLAB/Simulink simulation and experimental results were the validation and satisfactorily achieved. The test results of the driverless tractor robot in spraying water on a football field were satisfactory steering response and rapid braking.